Evolution of cross-cultural architectural decorative elements from a semiotic perspective: A comparative study of Ming-Qing Chinese and Malacca Baba-Nyonya architecture - Ren, Yujing; Masri, Mawar (Edelweiss Applied Science and Technology, 2025)
This research systematically analyzes the morphological characteristics, symbolic meanings, and evolutionary patterns of decorative elements in Ming-Qing Chinese and Malacca Baba-Nyonya architecture through a semiotic perspective. The study employs an interdisciplinary approach, integrating architectural semiotics theory with field research to construct an analytical framework encompassing morphological analysis, semiotic interpretation, and cross-cultural comparison. Findings reveal that geometric and natural patterns dominate Baba-Nyonya architecture, while animal patterns and character/symbol patterns predominate in Ming-Qing architecture. Decorative elements in cross-cultural transmission demonstrate three translation modes: form preservation-meaning preservation, form preservation-meaning transformation, and form transformation-meaning transformation. Baba-Nyonya architectural decorations exhibit more vibrant colors and higher pattern density, while symbolically transitioning from traditional hierarchical order and religious connotations toward commercial prosperity and family prosperity values. The research findings not only validate Eco’s theory of dual functions of architectural signs but also provide historical references and theoretical foundations for cross-cultural architectural design and cultural heritage preservation.